Who Wrote the First Novel "About Temurbek"!? - Jurayev, Jamoliddin; Adhamjon, Umarov (European Journal of Life Safety and Stability (2660-9630), 2021)
This articl gives information about the huge number of books regarding the life of Amir Temur, in fact that one of the first epic poem was written “Story about Temurbek” by Haydar Khorazmiy